Sex-Specific Risk Factors and Health Disparity Among Hepatitis C Positive Patients Receiving Pharmacotherapy for Opioid Use Disorder: Findings From a Propensity Matched Analysis. Issue 4 (18th July 2022) - Dennis, Brittany B.; Martin, Leslie J.; Naji, Leen; Akhtar, Daud; Cholankeril, George; Kim, Donghee; Sanger, Nitika; Hillmer, Alannah; Chawar, Caroul; D'Elia, Alessia; Panesar, Balpreet; Worster, Andrew; et al.
Abstract : Background: The incidence of opioid-related fatality has reached unparalleled levels across North America. Patients with comorbid hepatitis C virus (HCV) remain the most vulnerable and difficult to treat. Considering the unique challenges associated with this population, we aimed to re-examine the impact of HCV on response to medication assistant treatment for opioid use disorder and establish sex-specific risk factors affecting care. Methods: This study employs a multi-center prospective cohort design, with 1-year follow-up. Patients aged ≥18, receiving methadone for opioid use disorder were recruited from a network of outpatient opioid addiction treatment centers across Southern Ontario, Canada. Patients with ≥50% positive opioid urine screens over 1 year of follow-up were classified as poor responders. The prognostic impact of HCV on response was established using a propensity score matched analysis. Sex-specific regression models were constructed to evaluate risk factors for treatment response. Results: Among participants eligible for inclusion (n = 1234), HCV was prevalent in 25% (n = 307). HCV patients exhibited significantly higher rates of high-risk opioid consumption patterns 35.29% (standard deviation 0.478). Sex-specific examination revealed females with HCV incur a 2 times increased risk for high-risk opioid consumption behaviors (female odds ratio: 1.95, 95% confidence interval 1.23, 3.10; P = 0.01). Conclusions: Findings from this study establish the link between HCV and poor treatment response, with differentially higher risk among female patients. In light of the high potential for overdose among this population, concerted efforts are required for distinguishing the source for sex-based disparities, in addition to establishing trauma and gender informed treatment protocols.